Izbeglice (refugees), azilanti (asylum seekers) and ilegalni migranti (illegal migrants) in administrative and public discourse in Serbia : an overview of concepts in a diachronic perspective - Stojić Mitrović, Marta (Array, 2020)
The present discourse concerning asylum and irregular migration, with all its concepts and institutions, techniques and code of conduct, was introduced in the Republic of Serbia through the EU Accession process. As a prerequisite for visa liberalization with the EU (achieved in 2009), Serbia signed readmission agreements with the EU and its member-states and adopted the Asylum Law (Zakon o azilu 2007) and the Law on Foreigners (Zakon o strancima 2008). However, related notions and legal instruments existed in the periods that preceded it. In this text I offer a diachronic overview of conceptual and procedural differences and discuss their entanglements, merging, spilling over and confrontation. In such a way, my aim is to point out their use as political statements in particular, as performatives affecting national and international political contexts.